Enhancing the Interfacial Properties of Composites by Grafting Polyethylene Glycol and Polyvinyl Alcohol Onto a CF Surface. Issue 5 (4th March 2019) - Zhan, Yi‐Kai; Du, Shuai; He, Min; Zhang, Dao‐Hai; Liu, Yu‐Fei; Li, Li‐Ping
Abstract : In this study, a carboxy esterification reaction was used to graft the hydrophilic polymers polyethylene glycol (PEG) and polyvinyl alcohol (PVA) onto the surface of carbon fibers (CFs). The properties of the grafted CFs were investigated by scanning electron microscopy (SEM), atomic force microscopy (AFM), X‐ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TG) and through the measurement of interlaminar shear strength (ILSS). SEM enabled the graft morphology on CF surfaces to be determined. In comparisons of grafted and non‐grafted CFs, AFM indicated that the roughness was significantly improved; XPS showed that the concentration of oxygen‐containing functional groups increased by 186.1%; TG showed that the grafting rate of CF ‐grafted PEG ( CF ‐g‐PEG) was 0.5%, and that of CF ‐grafted PVA ( CF ‐g‐PVA) was 2.0%; and the ILSS of CF ‐g‐PEG and CF ‐g‐PVA increased by 22.7% and 43.0%, respectively. We conclude that esterification grafting is an effective method for modifying the physicochemical properties of CFs and improving the interfacial adhesion of composites. POLYM. ENG. SCI., 59:1043–1050, 2019. © 2019 Society of Plastics Engineers